Case Analysis and Gamification: Implementing Active Methods and Strategies for Teaching Innovation (Innovaciones Educativas, 2025)
Industrial civil engineering is a profession with a very solid scientific base. In Chile, it has begun to innovate the educational curricula with a curriculum based on competencies and learning outcomes. This has led academic institutions to adapt their methodologies and teaching strategies to improve professional training. In this context, the pedagogical systematization was based on a case analysis methodology with gamification strategies. The objective was to determine the effect of case analysis with gamification strategies as a didactic approach for teaching the concepts of innovation, competitiveness, entrepreneurship and creativity. Thirty-two students from Section B of the Innovation Management course participated. A didactic sequence of eight sessions was proposed, with a number of cases that were representative of the subject matter. To analyze the results, an analytical rubric was designed and validated, using the Course Experience Questionnaire (CEQ) adapted to the Chilean context by Marchant, Fauré and Abricot (2016). The results show, among other things, that students achieve the expected achievements for the curricular activity in a satisfactory manner when they encounter difficulties in the generic elements of the education. Regarding the formative experience and the dimensions evaluated, the students consider that the formative experience included quality teaching, that the proposed objectives were clear and achievable, and that the evaluation instruments were appropriate. In conclusion, the proposal of a didactic sequence with an active methodology improves academic performance and motivation.
Keywords: Methodology; Professional training; Engineering; Education; Simulation Game